Lessons About Best Interests Duty - Aaron Bruhn; Michael Miller (Australasian Accounting, Business and Finance Journal, 2014)
Financial advice is essentially a credence good, whose value is hard to assess. Yet in the Australian context the need for quality advice is growing, with self-sufficiency a growing trend and individuals facing significant complexity in their financial affairs. Recent regulatory proposals and reforms have been offered as a means to provide some comfort for consumers about the quality advice that they might receive, yet the challenge remains about what is meant by ‘quality’ in this area. By referring to recent high profile collapses, we describe some factors and features that are generally considered as examples of poor quality advice. In this manner, we offer bounds on what quality can be represented by, and outline factors that can be considered by individuals when assessing the quality of any service being offered.
Keywords: Best Interests Duty; Financial Planning; Wealth Management; Australia; Regulation